Secure delivery of multimedia data: a system model - Nguyen, Tien Ban (H. : ĐHQGHN, 2017)
In this paper, we propose a multimedia data delivery system model with secure solutions. This security is included both in data transmist..on and in data protection. The approach for the former is the combination between encryption methods and content authentication. The latter is solved by using watermarking method for the characteristics of possessive person as well as data user. These characteristics aie used to deal with contention in the case of copyright violation. The article also proposes the operation mechanisrq the basic communication models and the experimental diagrams for the proposed system.